ASSESSMENT OF JOB COMMITMENT OF SECONDARY SCHOOL TEACHERS IN OSUN STATE, NIGERIA - Akinwale, Ayotunde Samuel; Okotoni, Comfort Abosede (PEOPLE: International Journal of Social Sciences, 2019)
This study investigated the level of teachers’ job commitment to the teaching profession, teachers’ commitment to teaching and learning and teachers’ commitment to school in secondary schools in Osun State. These were with a view to assessing the level of teachers’ job commitment in the State. The study employed survey research design. The study population consisted of 6,922 secondary school teachers and 466 principals in Osun State while the sample for the study consisted of 720 teachers and 36 principals. Two validated instruments were used for the study, namely; Teachers’ Job Commitment Questionnaire for Teachers (TJCQT) and Teachers’ Job Commitment Questionnaire for Principals (TJCQP). Three research questions were raised in line with the objectives of the study. The research questions were answered using percentages.The results showed that the commitment of teachers in Osun State to the teaching profession, to teaching and learning and commitment to school was generally low in secondary schools in the State. The study recommended that government and school owners should employ strategies such as regular promotion, prompt payment of salaries and other emoluments, provision of adequate resources in schools, smooth and effective interaction between principals and teachers, high level of discipline in schools, involvement of teachers in decisions that affects them among other things in order to keep teachers committed to their job.